ANALISIS PERBEDAAN ANALISA HARGA SATUAN ITEM PEKERJAAN PADA RENCANA ANGGARAN BIAYA DAN PELAKSANAAN (Studi Kasus : Proyek Preservasi Jalan Lingkar Luar Kota Kupang) (Eternitas: Jurnal Teknik Sipil, 2022)
This study deals with differences in unit price analysis of work items on the planned budget and implementation due to changes in the coefficient based on labor and equipment production in implementation. This observation was carried out for five (5) work items on the Kupang City Outer Ring Road Preservation Project. The purpose of this study is to determine the differences in the coefficient of labor and equipment and to know the difference in unit price analysis of work items in the budget plan and the implementation due to changes in the coefficient based on the production of labor and equipment in implementation. The data needed to complete this research is primary data obtained from direct observation in the field, namely the effective working time in the field, the number of workers and equipment, the workforce and tools during the time observed and secondary data obtained from PT. Alamindah Cendanalestari namely the unit price analysis of work items and the coefficient of labor and equipment. From the description of the results of the analysis and discussion it is known that, the coefficient of labor in the implementation and the coefficient of labor estimated in the RAB has differences. The difference that occurs in the coefficient also causes the difference in unit price analysis. The difference in unit price analysis between RAB and implementation causes a change in profits.